A Statistical Summary of the Extent of Import Control in the United Kingdom Since the War - Hemming, M. F. W.; Miles, C. M.; Ray, G. F. (Review of Economic Studies, 1959)
M. F. W. Hemming, C. M. Miles, G. F. Ray; A Statistical Summary of the Extent of Import Control in the United Kingdom since the War1, The Review of Economi